Facing a Common Human Fate: Relating Global Identity and Climate Change Mitigation. Issue 3 (4th October 2021) - Loy, Laura S.; Reese, Gerhard; Spence, Alexa
Abstract : Collective efforts of the world community are required to mitigate global climate change. Understanding oneself as part of this world community might be crucial for individual behavior change reducing carbon emissions. We examined whether a global identity (i.e., the identification with all humans and a concern for their well‐being) is related to self‐reported climate‐protective behavior in two studies. In a German quota sample ( N  = 498), global identity was positively related to the personal and societal relevance people attributed to the issue of climate change and self‐reported climate‐protective behavior directly and indirectly through personal and societal relevance attribution. In a U.K. quota sample ( N  = 400), global identity was positively related to the relevance people attributed to a received news text on climate change. Moreover, global identity was positively related to three observed indicators of climate‐protective behavioral intentions after reading the news text, either directly or indirectly through relevance attribution. These results affirm the importance of a social identity perspective on climate protection. We suggest that the causal effects of global identity and ways to promote its cultivation should be investigated in more depth in future research.